Experiments with Lithic Tools: Understanding Starch Residues from Crop Harvesting. (25th April 2013) - Yang, X.; Ma, Z.; Li, Q.; Perry, L.; Huan, X.; Wan, Z.; Li, M.; Zheng, J.
<x xml:space="preserve">Abstract</x> Stone knives were used widely in Neolithic East Asia, presumably in the harvesting of grain crops, but their function has not been clearly understood due to the lack of study of residues from these tools. To address this issue, starch grain analysis was employed to study the residues on the surface of ancient stone knives and large amounts of starches were recovered. The sources of these starches, however, were not well understood, because harvesting of crops involves the cutting of stems rather than direct contact with starchy seeds. To determine whether harvesting could deposit these types of residues, we designed a simulation experiment using stone flakes to harvest ears of wheat, rice and foxtail millet, then analysed the residues on both the flakes and in the plant tissues. A large number of starch grains were found in the stems, including both typical morphotypes from seeds and newly described types that occur only in stems, which can be used as indicators of harvesting. Our study demonstrates that starch grains from residues on the surfaces of archaeological stone knives can indicate not only that the tools were used to harvest ears, but also the type of crops harvested.